A Bird in the Hand: Understanding the Trajectories of Development of Young Children and the Need for Action to Improve Outcomes. Issue 3 (September 2015) - Tayler, Collette; Cloney, Daniel; Niklas, Frank
THE ABILITIES AND CAPABILITIES young children bring into school accrue as a result of prior family, community and early children program experience, and they assist or impede transitions and ongoing progress in the first school years. In Australia, family contexts and children's early childhood education and care (ECEC) program pathways are diverse, and processes for addressing learning and development difficulties are at the discretion of the early educators who support children within typical everyday programs. The Australian E4Kids longitudinal study directly assessed the general cognitive ability and receptive and expressive language of a sample of 2498 three- and four-year-old children and tracked their progress into the early years of school. The abilities of these preschool 1 children are reported, along with associations with family background characteristics and the abilities trajectory of different sub-groups. Children who are at risk of poor outcomes as they progress toward school are the focus of this paper. Analyses address the differences between children's abilities at baseline measurement, characteristics of the participants' home environments and the trajectories of these children over three years. The findings provoke early consideration by educators of the context of children entering programs and the provision of more direct educational supports to children who are at risk of poor progress, both at home and in centres.